Challenging the Drug-Likeness Dogma for New Drug Discovery in Tuberculosis - Machado, Diana; Girardini, Miriam; Viveiros, Miguel; Pieroni, Marco (Frontiers in Microbiology, 2018)
The emergence of multi- and extensively drug resistant tuberculosis worldwide poses a great threat to human health and highlight the need to discover and develop new, effective and inexpensive antituberculosis agents. High-throughput screening assays against well-validated drug targets and structure based drug design have been employed to discover new lead compounds. However, the great majority fail to demonstrate any antimycobacterial activity when tested against Mycobacterium tuberculosis in a whole-cell screening assays. This is mainly due to some of the intrinsic properties of the bacilli, such as the extremely low permeability of its cell wall, slow growth, drug resistance, drug tolerance and persistence. In this sense, understanding the pathways involved in M. tuberculosis drug tolerance, persistence and pathogenesis, may reveal new approaches for drug development. Moreover, the need for compounds presenting a novel mode of action is of utmost importance due to the emergence of resistance not only to the currently used antituberculosis agents, but also to those in the pipeline. Cheminformatics studies have shown that drugs endowed with anti-tuberculosis activity have the peculiarity of being more lipophilic than many other antibacterials, likely because this leads to improved cell penetration through the extremely waxy mycobacterial cell wall. Moreover, the interaction of the lipophilic moiety with the membrane alters its stability and functional integrity due to the disruption of the proton motive force, resulting in cell death. When a ligand-based medicinal chemistry campaign is ongoing, it is always difficult to predict whether a chemical modification or a functional group would be suitable for improving the activity. Nevertheless, in the “instruction manual” of medicinal chemists, certain functional groups or certain physicochemical characteristics (i.e. high lipophilicity) are considered red flags to look out for in order to safeguard drug-likeness and avoid attritions in the drug discovery process. In this review, we describe how antituberculosis compounds challenge established rules such as the Lipinski’s rule of five, and how medicinal chemistry for antituberculosis compounds must be thought beyond such dogmatic schemes.